Effects of Anticholinergic Drugs Used for the Therapy of Overactive Bladder on P-Glycoprotein Activity - Wakuda, Hirokazu; Okura, Takashi; Maruyama-Fumoto, Kana; Kagota, Satomi; Ito, Yoshihiko; Miyauchi-Wakuda, Shino; Otani, Naoyuki; Uemura, Naoto; Yamada, Shizuo; Shinozuka, Kazumasa (Biological & pharmaceutical bulletin, 2019)
We evaluated the effects of anticholinergic drugs principally used for the therapy of overactive bladder (OAB) on the activity of P-glycoprotein, an efflux transport protein, in Caco-2 cells. The time-dependent changes in the fluorescence of residual rhodamine 123, a P-glycoprotein activity marker, in the apical region of Caco-2 cells were measured in the presence of anticholinergic drugs using time-lapse confocal laser scanning microscopy. The effect of anticholinergic drugs on human P-glycoprotein ATPase activity was also measured. The fluorescence of residual rhodamine 123 in untreated Caco-2 cells decreased over time. The gradual decrease in the fluorescence was significantly inhibited by treatment with cyclosporine A, darifenacin, and trospium. In contrast, oxybutynin, N-desethyl-oxybutynin (DEOB), propiverine, and its active metabolites (M-1, M-2), imidafenacin, solifenacin, or tolterodine had little effect on the efflux of rhodamine 123. P-Glycoprotein ATPase activity was increased by darifenacin. Darifenacin and trospium reduced the rhodamine 123 transfer across the apical cell membrane. These data suggest that darifenacin and trospium interact with P-glycoprotein. Additionally, darifenacin influenced P-glycoprotein ATPase activity. These results suggest that darifenacin may be a substrate of P-glycoprotein. This study is the first paper to test simultaneously the effects of 10 anticholinergic drugs used currently for the therapy of OAB, on the P-glycoprotein.